2001
DOI: 10.1210/endo.142.11.8511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IL-6 on IGF Binding Protein-3: A Study in IL-6 Transgenic Mice and in Patients with Systemic Juvenile Idiopathic Arthritis

Abstract: Stunted growth is a common complication of childhood diseases characterized by chronic inflammation or infections.We previously demonstrated that NSE/hIL-6 transgenic mice, overexpressing the inflammatory cytokine IL-6 since early phase of life, showed a marked growth defect associated with decreased IGF-I levels, suggesting that IL-6 is one of the factors involved in stunted growth complicating chronic inflammation in childhood. Here we show that NSE/hIL-6 mice have normal liver IGF-I production, decreased le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
11

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 127 publications
(45 citation statements)
references
References 50 publications
1
33
0
11
Order By: Relevance
“…The IL6-overexpressing mice exhibit a defective growth phenotype with a size reduction of 50-70% compared with normal non-transgenic littermates. The growth retardation in these mice was associated with decreased levels of IGF1 and IGF1-binding protein 3 (IGFBP3), yet with normal distribution of GH pituitary cells and GH production (De Benedetti et al 1997, De Benedetti et al 2001. This finding is consistent with the situation in patients with JIA where high circulating levels of IL6 are negatively correlated with IGF1 and IGFBP3 levels (Gaspari et al 2011).…”
Section: Impact Of Inflammation On Bone Growthsupporting
confidence: 61%
“…The IL6-overexpressing mice exhibit a defective growth phenotype with a size reduction of 50-70% compared with normal non-transgenic littermates. The growth retardation in these mice was associated with decreased levels of IGF1 and IGF1-binding protein 3 (IGFBP3), yet with normal distribution of GH pituitary cells and GH production (De Benedetti et al 1997, De Benedetti et al 2001. This finding is consistent with the situation in patients with JIA where high circulating levels of IL6 are negatively correlated with IGF1 and IGFBP3 levels (Gaspari et al 2011).…”
Section: Impact Of Inflammation On Bone Growthsupporting
confidence: 61%
“…However, in 1999 (16) a study in adult patients with CF reported normal spontaneous GH secretion and release after stimulation with arginine. The report a few years later of low serum IGF-I, increased IGFBP-3 proteolysis and poor growth in transgenic mice overexpressing interleukin (IL)-6 supports the hypothesis that inflammatory mediators per se could modulate the IGF/IGFBP system (17,18).…”
Section: Introductionmentioning
confidence: 74%
“…These observations demonstrate that chronic overproduction of IL-6 can cause a growth defect, and that this growth defect is associated with abnormalities of the IGF-1 system similar to those found in patients. In further support of the relationship between IL-6 and the IGF-1 system, in patients with systemic JIA, circulating levels of IL-6 are inversely correlated with levels of IGF-1 and IGFBP-3 (46,49).…”
Section: Role Of Il-6 In Systemic Jiamentioning
confidence: 81%
“…IL-6-transgenic mice with high circulating levels of IL-6 since birth show a decreased rate of growth, attaining 50-60% of the size of their wild-type littermates as adults (46). Similar to patients with systemic JIA (47,48), IL-6-transgenic mice have normal growth hormone production but low levels of insulin-like growth factor 1 (IGF-1) and IGF binding protein 3 (IGFBP-3) (46,49). These observations demonstrate that chronic overproduction of IL-6 can cause a growth defect, and that this growth defect is associated with abnormalities of the IGF-1 system similar to those found in patients.…”
Section: Role Of Il-6 In Systemic Jiamentioning
confidence: 99%